Evaluation of orange-fleshed sweetpotato genotypes for yield and yield contributing parameters in two environments - WIWIT RAHAJENG; ST. A. RAHAYUNINGSIH (Smujo International, 2017)
Rahajeng W, Rahayuningsih SA. 2017. Evaluation for yield and yield contributing parameters of orange-fleshed sweetpotato genotypes in two environments. Nusantara Bioscience 9: 275-281. Orange-fleshed sweetpotatoe (OFSP) is one of the most important sources of betacaroten and carbohydrates. OFSP showed varying responses to different environments, depending on the adaptability of the genotypes. The objective of this study was to evaluate the correlation between yield and yield component of OFSP genotypes at two different agroclimatological environments (Mojokerto and Blitar) from May to September 2013. Twenty four OFSP genotypes (twenty two clones and two varieties as the check) were used in this study and arranged in a randomized complete block design with three replications. Results showed that responses of OFSP genotypes to the environments varied and genotypes had highly significantly affected all parameters. Based on the criteria of high yield, amylum content, and dry matter production four clones were selected (MSU 09008-54, MSU 07009-113, MSU 07025-45, and MSU 09025-71) from Blitar and two clones (MSU 07009-113 and MSU 070-64) from Mojokerto. Clone MSU 07009-113 showed good performance in both environments for yield, amylum content, and dry matter production parameters. The result of the correlation analysis reveals that root yield is highly significant and positively correlated with dry matter production, number of roots, diameter of root, and harvest index in two locations (Blitar and Mojokerto). Based on the correlation and path analysis, dry matter production, root diameter, and harvest index can be used as an effective indicators selection for high yield OFSP genotypes.